2014
DOI: 10.1186/1472-6882-14-157
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing and antibacterial properties of methanolic extract of Pupalia lappacea Juss in rats

Abstract: BackgroundWound healing is a natural process that enables tissue repair after an injury. To shorten its duration and minimize associated complications, wounds are treated with medications. Currently there is a growing interest in the use of alternative wound dressing agents such as plant extracts. One plant used traditionally in wound treatment is Pupalia lappacea. In view of its use in wound care, we investigated the wound healing activities of 80% methanolic leave extract of Pupalia lappacea using excision, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
0
35
1
1
Order By: Relevance
“…However, differences were observed with coumarins (Dibala et al, 2016), alkaloids (Enemali and Udedi, 2018) and tannins (Elya et al, 2015). Regarding P. lappacea, a similitude was also observed with previous study (Udegbunam et al, 2014;Hoekou et al, 2012). Contrary to our results, alkaloids and tannins have been detected in ethanolic extract.…”
Section: Discussioncontrasting
confidence: 99%
“…However, differences were observed with coumarins (Dibala et al, 2016), alkaloids (Enemali and Udedi, 2018) and tannins (Elya et al, 2015). Regarding P. lappacea, a similitude was also observed with previous study (Udegbunam et al, 2014;Hoekou et al, 2012). Contrary to our results, alkaloids and tannins have been detected in ethanolic extract.…”
Section: Discussioncontrasting
confidence: 99%
“…The ethanol and chloroform extracts also exhibited high rate of wound closure [25]. However, Udegbunam et al [26] also reported that higher concentrations (10% and 20% (w/v) ointment of methanol leaf extract of P. lappacea) significantly (p < 0.05) accelerated wound healing, thereby the 20% ointment having the highest percentage wound contraction and rate of epithelialization. The extract also exhibited antimicrobial activity with MIC of 3.0-9.0 mg/mL and MBC of 7-10 mg/ mL against Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilis.…”
Section: Methods Used For Pinpointing Herbal Materials and Natural Prmentioning
confidence: 99%
“…The petroleum ether extract of the plant has an excellent antibacterial activity against MRSA with an IC50 value of 7.8 μg/mL (82). The extract of Laurus nobilis leaves has also shown a potent anti-MRSA activity (ZOI = 25 mm) and an antiquorum sensing activity (>17 mm) (46). Ethyl acetate fraction from Cinnamomum iners standardized leave has a strong antibacterial activity, especially against MRSA and E. coli with the MIC values of 100 and 200 μg/mL, respectively.…”
Section: Family Lauraceaementioning
confidence: 99%